Do Humanity and Duty Conflict? A Moral-Philosophical Reading - Bhatta, Damaru Chandra (Mindscape: A Journal of English & Cultural Studies, 2023)
The purpose of this article is to explore the idea how humanity (human values) and duty conflict in many circumstances. I believe that they cannot be done at the same time and when one tries to do one of them alone, the other comes on the way. And to prove this, I have referred to characters and quotes from different areas of knowledge such as Buddhist and Hindu religions, literature, law, education, medical profession, war, army and, especially from the Bhagavad-Gita. Humanity or human values are truth, right conduct, love, peace, and non-violence. All religions are formed under this basic foundation. Duty is an obligatory act or a course of action that is to be fulfilled according to one’s position, social custom, law, religion, or morality of a particular culture.